The ocean in the school : Pacific Islander students transforming their university - Bonus, Rick, 1962- (Duke University Press, 2020)
"Drawing on formal and informal ethnographic research with Pacific Islander students at the University of Washington, THE OCEAN IN THE SCHOOL offers a timely examination of how college students transform their universities from within. Rick Bonus seeks to disrupt standardized notions of success and failure in higher education by asking not how students fail at school, but how schools fail their students of color. Analyzing how schools exist not as neutral institutions, but rather as entities with racialized, classed, gendered, and sexualized identities, Bonus explores how students of color navigate these school identities and form communities and modes of critique. Drawing on the ocean as a metaphor for that which ties Pacific Islander students together, this book traces how oceanic belonging fosters community for students of color in predominately white institutions, and offers a model for disrupting histories of exclusion. THE OCEAN IN THE SCHOOL uses the localized activities of student activism and community building at the University of Washington to ask larger questions about the metrics we use to measure student university success, and the purpose of higher education"--